Personality traits, loneliness, and attitudes toward aloneness in adolescence. (December 2013) - Teppers, Eveline; Klimstra, Theo A.; Damme, Carolien Van; Luyckx, Koen; Vanhalst, Janne; Goossens, Luc
Within a dual-level model of personality, loneliness, and attitudes toward aloneness can be regarded as phase-specific adaptations that are influenced by personality traits. Therefore, we examined the associations between personality traits (i.e., the Big Five, sociotropy, and autonomy), loneliness, and attitudes toward aloneness in two samples of late adolescents ( N  = 1388 and N  = 419). A specific pattern of associations was found that replicated across samples. Lower scores on agreeableness and stronger concerns about independence (i.e., greater autonomy) were positive predictors of both peer-related and parent-related loneliness. Extraversion was a predictor of lower affinity for and greater aversion to aloneness. The other personality traits were predictors of a particular type of loneliness or a specific attitude toward aloneness.